2014
DOI: 10.1542/peds.2014-0992
|View full text |Cite
|
Sign up to set email alerts
|

Attention-Deficit/Hyperactivity Disorder and Substance Abuse

Abstract: Attention-deficit/hyperactivity disorder (ADHD) and substance use disorders are inextricably intertwined. Children with ADHD are more likely than peers to develop substance use disorders. Treatment with stimulants may reduce the risk of substance use disorders, but stimulants are a class of medication with significant abuse and diversion potential. The objectives of this clinical report were to present practical strategies for reducing the risk of substance use disorders in patients with ADHD and suggestions f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
60
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 107 publications
(70 citation statements)
references
References 75 publications
9
60
0
1
Order By: Relevance
“…In addition, stimulants such as Ritalin normalize the hyperactivity associated with ADHD, and, consistent with this, we found that cocaine-induced locomotor sensitization was blunted in mice that received extended periods of sensory stimulation. Finally, children with ADHD have an increased risk for the development of drug abuse and addiction (Harstad and Levy, 2014), and we found that mice that received sensory stimulation displayed an increase in the rewarding effects of cocaine, indicating an enhanced vulnerability to drugs of abuse. Thus, the excessive sensory stimulation paradigm provides a highly relevant model to understand how environments that contain excessive and ill-patterned stimuli influence behavioral outcomes, change neuroplasticity, and influence the propensity to the development of neuropsychiatric disorders, such as ADHD and addiction.…”
Section: Discussionmentioning
confidence: 82%
“…In addition, stimulants such as Ritalin normalize the hyperactivity associated with ADHD, and, consistent with this, we found that cocaine-induced locomotor sensitization was blunted in mice that received extended periods of sensory stimulation. Finally, children with ADHD have an increased risk for the development of drug abuse and addiction (Harstad and Levy, 2014), and we found that mice that received sensory stimulation displayed an increase in the rewarding effects of cocaine, indicating an enhanced vulnerability to drugs of abuse. Thus, the excessive sensory stimulation paradigm provides a highly relevant model to understand how environments that contain excessive and ill-patterned stimuli influence behavioral outcomes, change neuroplasticity, and influence the propensity to the development of neuropsychiatric disorders, such as ADHD and addiction.…”
Section: Discussionmentioning
confidence: 82%
“…Children with these disorders are at increased risk for substance abuse and addiction during young adulthood (Harstad and Levy, 2014; Levy et al, 2014; Salvo et al, 2012; Zonnevylle-Bender et al, 2007), including abuse of psychostimulant medications used to treat ADHD symptoms (Faraone and Wilens, 2007; Wilens et al, 2008). The results from this study suggest that early-life antipsychotic drug exposure may raise sensitivity to some behavioral effects of psychostimulants later in life, eliciting concern regarding greater substance abuse potential in children treated with antipsychotic drugs.…”
Section: Discussionmentioning
confidence: 99%
“…1 ADHD often results in impairments in multiple domains, including academics, interpersonal relationships, classroom behavior, and self-esteem. 2 ADHD is associated with higher rates of other psychiatric disorders, 3, 4 substance abuse, 57 and suicide. 3 These negative effects underscore the importance of accurately diagnosing children and adolescents with ADHD and monitoring treatment effects over time.…”
Section: Introductionmentioning
confidence: 99%